2004
DOI: 10.1002/humu.9224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of theAPCandMYHgenes in Czech families affected by FAP or multiple adenomas: 13 novel mutations

Abstract: Familial adenomatous polyposis (FAP) is an autosomal dominant predisposition to colorectal cancer and is caused by germline mutations in the adenomatous polyposis coli gene. The most prominent clinical manifestation is the presence of hundreds to thousands of colorectal polyps.A milder phenotype is found in patients affected with AFAP/ multiple adenomas. We screened the entire APC coding region using the combination of DGGE, PTT and direct sequencing and identified causative mutations in 52 of 77 patients. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Whether identical at genome level, remains to be seen. The frequent Wve base pair deletions at codons 1,061 and 1,309 detected in 5 (7.3%) and eight families (11.6%), respectively, is in accordance with other reports (Miyoshi et al 1992;Vandrovcova et al 2004), although signiWcantly higher and lower proportions have been reported (Nagase and Nakamura 1993;De Rosa et al 2004;García-Lozano et al 2005). Since the frequent 5 bp deletions of 1061 and 1309 are straightforwardly detected irrespective of methods being applied, the ratio between these two should represent solid indicators of ethnic variations in mutation spectra.…”
Section: Mutation Spectrumsupporting
confidence: 89%
“…Whether identical at genome level, remains to be seen. The frequent Wve base pair deletions at codons 1,061 and 1,309 detected in 5 (7.3%) and eight families (11.6%), respectively, is in accordance with other reports (Miyoshi et al 1992;Vandrovcova et al 2004), although signiWcantly higher and lower proportions have been reported (Nagase and Nakamura 1993;De Rosa et al 2004;García-Lozano et al 2005). Since the frequent 5 bp deletions of 1061 and 1309 are straightforwardly detected irrespective of methods being applied, the ratio between these two should represent solid indicators of ethnic variations in mutation spectra.…”
Section: Mutation Spectrumsupporting
confidence: 89%
“…While some groups have conducted whole MYH gene mutation screening in multiple adenoma patients to identify uncommon, but otherwise important pathogenic MYH mutations [9,[11][12][13][20][21][22], some published series have restricted mutation testing to only include the Y165C and G382D mutations [19,23]. Heterozygous Y165C and G382D mutation carriers may be at slightly increased risk of developing colorectal adenomas and cancer, however, a definitive estimate of this risk has not been determined with certainty [9,12,13,19,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the APC negative FAP or AFAP cases have recently been found to be attributable to MAP (De Rosa, et al, 2004;Gismondi, et al, 2004;Vandrovcova, et al, 2004;Venesio, et al, 2004;Wang, et al, 2004). Patients with biallelic MYH mutations seem to have a phenotype partially overlapping with FAP, although MAP patients tend to have fewer adenomas and more advanced age at disease onset (Jones, et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%